2023
DOI: 10.2147/copd.s395492
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Communal Molecular Mechanism Between Chronic Obstructive Pulmonary Disease and Osteoporosis

Abstract: Background: Chronic obstructive pulmonary disease (COPD) patients with osteoporosis (OP) usually experience more frequent exacerbations, worse quality of life, and heavier economic burden, however, few studies have investigated common molecular mechanisms of COPD and OP. Objective: To explore the relationship between COPD and OP through bioinformatics analysis. Methods: The miRNA microarray data of COPD and OP were retrieved from the Gene Expression Database (GEO), and the differentially expressed microRNAs (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Two randomized controlled clinical trials [35,36] have found a putative common link between COPD and BMD through the activity of osteoclast activation indicators, such as matrix metalloproteinases. Two similar miRNAs (miR-23a-5p and miR-194-3p) were discovered to be present in the peripheral blood of COPD and OP patients by a recent bioinformatics investigation [37] . The ndings support the hypothesis that COPD and OP may share a common pathogenic molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled clinical trials [35,36] have found a putative common link between COPD and BMD through the activity of osteoclast activation indicators, such as matrix metalloproteinases. Two similar miRNAs (miR-23a-5p and miR-194-3p) were discovered to be present in the peripheral blood of COPD and OP patients by a recent bioinformatics investigation [37] . The ndings support the hypothesis that COPD and OP may share a common pathogenic molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%